Предмет: Алгебра,
автор: dgvcffgggfg
Решить уравнения:
(x+1)(x+2)-(x-3)(x+4)=0
Ответы
Автор ответа:
0
x²+2x+x+2-(x²+4x-3x-12)=0
x²+3x+2-x²-x+12=0
2x+14=0
2x=-14
x=-7
Ответ: x=-7
Автор ответа:
4
( х + 1 ) ( х + 2 ) - ( х - 3 ) ( х + 4 ) = 0
х² + 2х + х + 2 - ( х²+ 4х - 3х - 12 ) = 0
х² + 2х + х + 2 - х² - 4х + 3х + 12 = 0
2х + 14 = 0
2х = -14
х = (-14) ÷ 2
х = -7.
Ответ : х = -7.
________________________________
Удачи))))
Похожие вопросы
Предмет: Русский язык,
автор: muradaliev053
Предмет: Литература,
автор: nastenaka1988
Предмет: Алгебра,
автор: angelinanigmatulina7
Предмет: Биология,
автор: Анютя1
Предмет: Литература,
автор: kolyakolya1210